2010
DOI: 10.1016/j.tiv.2010.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR activates the ERK1/2 kinases and stimulates the proliferation of the monkey kidney-derived cell line Vero-E6

Abstract: a b s t r a c tMicrocystin-LR (MCLR) is a peptide produced by freshwater cyanobacteria that induces severe hepatotoxicity in humans and animals. MCLR is also a potent tumour promoter and it has been proposed that this activity is mediated by the inhibition of protein phosphatases PP1/PP2A, possibly through the activation of proto-oncogenes c-jun, c-fos and c-myc. However, the mechanisms underlying MCLR-induced tumour promotion are still largely unknown, particularly in non-liver cells. In previous studies we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 48 publications
4
41
1
Order By: Relevance
“…Recent reports suggest that MCs modulate PPs activity not only by the direct inhibition of enzyme activity, but also through the regulation of protein expression [16][17][18][19][94][95][96][97]. PP1 and PP2A inhibition induces the disruption of the dynamic equilibrium of protein phosphorylation/dephosphorylation, leading to the damage of numerous cellular processes such as cytoskeleton organization, Wnt, Akt, p38, c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase 1/2 (ERK1/2) of mitogen-activated protein kinase (MAPK) signaling pathways, metabolism and cell cycle [20,[98][99][100][101] (Fig. 4).…”
Section: Modulation Of Pp1 and Pp2a Activitiesmentioning
confidence: 99%
“…Recent reports suggest that MCs modulate PPs activity not only by the direct inhibition of enzyme activity, but also through the regulation of protein expression [16][17][18][19][94][95][96][97]. PP1 and PP2A inhibition induces the disruption of the dynamic equilibrium of protein phosphorylation/dephosphorylation, leading to the damage of numerous cellular processes such as cytoskeleton organization, Wnt, Akt, p38, c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase 1/2 (ERK1/2) of mitogen-activated protein kinase (MAPK) signaling pathways, metabolism and cell cycle [20,[98][99][100][101] (Fig. 4).…”
Section: Modulation Of Pp1 and Pp2a Activitiesmentioning
confidence: 99%
“…Few studies support this hypothesis: (1) Li et al [68] reported the activation of proto-oncogenes c-jun, c-fos and c-myc by a cyanobacterial extract containing microcystins in rat liver, kidney and testis; (2) Zhu et al [69] demonstrated that MCLR induces the transformation of immortalized colorectal crypt cells through the constitutive activation of AKT and MAPK (p38 and JNK) cascades. Our team has evaluated the effect of MCLR in Vero-E6 cell line proliferation through the BrdU incorporation assay that evaluates the G1/S transition in cell cycle [28]. We showed that MCLR (1 to 10 nM) induces a significant increase in Vero cells proliferation with a maximum of 2.2 fold increase at 5 nM [28].…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Our team has evaluated the effect of MCLR in Vero-E6 cell line proliferation through the BrdU incorporation assay that evaluates the G1/S transition in cell cycle [28]. We showed that MCLR (1 to 10 nM) induces a significant increase in Vero cells proliferation with a maximum of 2.2 fold increase at 5 nM [28]. We further analyzed the expression of MAPK (ERK1/2, JNK and p38) by Western-blot and concluded that MCLR stimulates Vero cells proliferation by the activation of the ERK1/2 signaling pathway [28].…”
Section: Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike c-myc, PP2A is generally regarded as a tumor suppressor (Janssens et al, 2005). Several studies have shown that PP2A might be able to affect the phosphorylation status of threonine 58 and serine 62 of c-myc in the direct or indirect pathways (Arnold and Sears, 2008;Dias et al, 2010;Henriksson et al, 1993;Lutterbach and Hann, 1994;Pulverer et al, 1994;Takumi et al, 2010). So, theoretically, given its potent effect on PP2A activity, MC-LR might be able to regulate c-myc protein stability.…”
Section: Introductionmentioning
confidence: 99%